1980
DOI: 10.1002/ardp.19803130409
|View full text |Cite
|
Sign up to set email alerts
|

Hemmung der Prostaglandinsynthetase durch Flavonoide und Phenolderivate im Vergleich mit deren O2−•‐Radikalfänger‐eigenschaften

Abstract: Eine Hemmung der Cyclooxygenase‐Reaktion bei der Prostaglandinbildung des Rattennierenmarks in vitro ist durch verschiedene Flavonoide mit o‐Dihydroxystrukturen möglich. Diese Flavonoide mit einer Brenzcatechin‐Anordnung im Molekül besitzen ausgeprägte Radikalfängereigenschaften für Peroxid‐Anion‐Radikale. Dagegen können einige Flavonoide und Phenolderivate, die starke O2−•‐Radikalfänger sind, die Prostaglandinsynthetase aber auch aktivieren oder unbeeinflußt lassen. Eine Korrelation zwischen den Radikalfänger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Quercetin and catechin are more hydrophilic than rutin, and catechin which is the best inhibitor out of these three has a nonplanar conformation. These findings confirm earlier data by Bau mann et al [ 13] who showed that the capacity of flavonoids to inhibit the PGES in a rat renal medulla homogenate does not depend on their radical scavenger properties. Similar results were obtained by Vanderhoek and Lands [25] who found no correlation between the oxidation potential of different antioxi dants and their capacity to inhibit PGES in microsomes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Quercetin and catechin are more hydrophilic than rutin, and catechin which is the best inhibitor out of these three has a nonplanar conformation. These findings confirm earlier data by Bau mann et al [ 13] who showed that the capacity of flavonoids to inhibit the PGES in a rat renal medulla homogenate does not depend on their radical scavenger properties. Similar results were obtained by Vanderhoek and Lands [25] who found no correlation between the oxidation potential of different antioxi dants and their capacity to inhibit PGES in microsomes.…”
Section: Discussionsupporting
confidence: 82%
“…[5], inhibition of histamine re lease from basophils and mast cells [6. 7], inhibition of 5-lipoxygenase [8][9][10] or inhibi tion of prostaglandin endoperoxide synthase (PGES) [11][12][13], An antiaggregatory effect has been proposed to be due to inhibition of cAMP phosphodiesterase [14], inhibition of PGES [15][16][17] or binding to platelet mem branes and scavenging of free radicals and stimulation of PGES, resulting in increased endothelial formation of prostaglandins [18]. These studies clearly indicate that added fla vonoids are able to inhibit the PGES of sev eral cell types in vivo as well as other enzyme systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, possible inhibition of platelet cyclo-oxygenase by flavonoids cannot be implied as the mechanism of inhibition of aggregation by ADP or thrombin, because it has been demonstrated that washed human platelets aggregate in the presence of ADP or thrombin independently of the formation of prostaglandin endoperoxide and thromboxane A 2 [33]. Flavonoids may also inhibit the platelet release reaction, because they are scavengers of free radicals [32,34]. Such a mechanism of action has been demonstrated for the effect of 2,3-dihydrobenzoic acid and other ortho-or paradiphenols on platelet function I351.…”
Section: Discussionmentioning
confidence: 99%
“…Phloretin also inhibits several membrane transport mechanisms [30]. Flavonoids have been shown to inhibit prostaglandin synthetase [31,32]. Nevertheless, possible inhibition of platelet cyclo-oxygenase by flavonoids cannot be implied as the mechanism of inhibition of aggregation by ADP or thrombin, because it has been demonstrated that washed human platelets aggregate in the presence of ADP or thrombin independently of the formation of prostaglandin endoperoxide and thromboxane A 2 [33].…”
Section: Discussionmentioning
confidence: 99%
“…1 H (400 MHz)-and 13 C (100 MHz)-NMR spectra were acquired with a Jeol JNM A-400 spectrometer. Rotating frame Overhauser enhancement spectroscopy (ROESY) spectra at 600.0 MHz ( 1 H) and 150.6 MHz ( 13 C) were taken with a Jeol ECA-600 spectrometer by a combination of the Ruben-States-Haberkorn procedure (States) and time proportional phase increment (TPPI).…”
Section: Methodsmentioning
confidence: 99%